Current Topics in Anemia - Khan, Jesmine (IntechOpen, 2018)
This book deals with a very common condition, anemia, which might interest not only the physicians but also other healthcare professionals and researchers dealing with anemic patients. The objective of this book was to collect and compile up-to-date information from reputable researchers of different countries of the world to disseminate the latest information about the common types of anemia in some specific physiological and pathological conditions including pathophysiology and the use of algorithms as a tool to minimize the laboratory tests and accurate diagnosis of the underlying cause. In total, there are 13 chapters in this book where the authors shared their research findings and real-life experiences in managing their patients with anemia.